Distinguishing between natural and anthropogenic sources of arsenic in soils from the Giant mine, Northwest Territories and the North Brookfield mine, Nova Scotia - Wrye, Lori Ann (2008)
Thesis (Master, Geological Sciences & Geological Engineering) -- Queen's University, 2008-09-29 17:21:50.73 Anthropogenic and geogenic sources of arsenic (As) have been identified in mining-impacted soils from the Giant mine (1948-1999), NT and the North Brookfield mine (1886-1906), NS. Both used roasting to extract gold from the arsenopyrite ore, decomposing it to As-bearing iron oxides (roaster oxides or RO) containing As, and releasing As3+-bearing arsenic trioxide (As2O3). Arsenic trioxide is considered highly soluble with the dissolved As3+ species being more mobile and toxic than other oxidation states. Soil profiles from the Giant mine show elevated As and antimony (Sb) at the surface (As=140-3300ppm) and decreasing concentrations with depth (As=22-600ppm). Surface soils contain anthropogenically-derived As2O3 identified using synchrotron methods (µXRD, µXANES) and environmental SEM. The persistence of As2O3 is attributed to Sb in As2O3 grains, dry climate and high organics in the soils. Anthropogenically-derived RO of maghemite (containing both As3+ and As5+) and natural arsenopyrite were observed. Sequential selective extractions (SSE) from surface soils show between 20% and 75% of As extracted in the crystalline iron-oxide phase is attributed to As2O3 and RO, while at depth As is bound by organics in the weaker leaches. North Brookfield mine soils show lower total As (2ppm to 45ppm) except near the roaster (4300ppm). No As2O3 was identified, probably due to the smaller scale and age of the mine, lower organic content and the lack of Sb. As-bearing phases include RO of hematite (As5+), As-rich rims on titanium-oxides, and As associated with clays and goethite. Adjacent to the roaster, SSE show As was also in the amorphous iron-oxide phase, also shown by As in arsenopyrite weathering rims. There are many differences between the North Brookfield and Giant mine soils including roasting techniques which produced different RO mineralogy, the scale of mining, climate, soil type, and the presence of ...